Investigating the effect of explicit and implicit instruction on the acquisition of verb + noun collocations: a case of L2 Egyptian learners - Kamal, Omneya Hesham (AUC Knowledge Fountain, 2014)
This study examines the effect of explicit and implicit instruction on the acquisition of verb + noun collocations. It also investigates L2 learners' attitudes about learning collocations both explicitly and implicitly. Forty intermediate level Egyptian L2 learners of English were given a collocations familiarity test from which the researcher chose the 21 least familiar target collocations to include in the study. Two experimental groups composed of 20 participants each were taught the target collocations through reading, listening and speaking activities. One group was taught with the explicit method and the other was taught with the implicit method. A post-test was administered to both groups assessing both their receptive and productive acquisition of the target collocations. A Likert scale survey was conducted on the 40 participants to investigate the students' attitudes toward learning collocations. The results of the t-test indicated that the group of learners who learned collocations explicitly significantly improved their receptive and productive knowledge of the verb + noun collocations. The general attitude of both groups about learning collocations was positive, as most of the participants expressed interest in learning collocations in the future and felt that that learning collocations would raise their language proficiency level.